Chiral Heteroditopic Baskets Designed from Triazolated Calixarenes and Short Peptides. Issue 35 (22nd July 2016) - Gorbunov, Alexander; Sokolova, Nadezhda; Kudryashova, Elena; Nenajdenko, Valentine; Kovalev, Vladimir; Vatsouro, Ivan
Abstract: Cone calix[4]arenes and calix[6]arenes bearing two, three, and four short peptide units each having two chiral carbon atoms were prepared. The syntheses were performed by using an efficient modular approach that includes the Ugi preparation of the azido‐peptide followed by its reactions with the propargylated calixarenes under CuAAC (Cu I ‐catalyzed azide–alkyne cycloaddition) conditions. The three novel multitopic hosts were probed for their ability to bind metal ions by UV titration, and showed the highest complexation efficiency towards copper(II) and lead(II). These two cations possessed quite different complexation modes with copper(II) bound predominantly by multiple‐triazole sites, in contrast to lead(II), which is stabilized mainly by multiple interactions with amide groups of the peptide units. Circular dichroism data for the free chiral hosts, their equimolar mixtures with copper(II) perchlorate and lead(II) perchlorate, and for tertiary mixtures of all three compounds showed the formation of mono‐ and binuclear complexes, or a switching behavior, depending on the structure of the host and the addition order of the cations. Abstract : Turn ditopic ! Sophisticated chiral heteroditopic hosts capable of interactions with a pair of cations may be easily prepared through Cu I ‐catalyzed azide–alkyne cycloaddition reactions from narrow‐rim propargylated calixarenes and azido‐peptides. The hosts created demonstrate a direction‐independent binuclear complexation, cation substitution/switching, or ordered binuclear complexation when interacting with Cu 2+ and Pb 2+ ions (see figure).